Derivation of New Threshold of Toxicological Concern Values for Exposure via Inhalation for Environmentally-Relevant Chemicals - Nelms, Mark D.; Patlewicz, Grace (Frontiers in Toxicology, 2020)
The requirements of amended Toxic Substances Control Act (TSCA) stipulates that the US Environmental Protection Agency (US EPA) evaluate existing chemicals and make risk based assessments. There are ~33000 substances that are active in commerce on the TSCA public non confidential inventory, many of which lack available toxicity and exposure information to inform risk-based decision making. One approach to facilitate the assessment of these substances being considered is the Threshold of Toxicological Concern (TTC). TTC values are intended to identify safe levels of exposure for data poor substances. TTC values derived based on non-cancer data notably by Munro et al. (1996) are well established and are in routine use for food additive applications however far less attention has been focused on developing TTC values where inhalation is the route of exposure. Here, an effort was made to derive new inhalation TTC values using the EPA’s Toxicity Values database, ToxValDB. A total of 4703 substances captured in ToxValDB were assigned into their respective TTC categories using the Kroes module within the Toxtree software tool and custom profilers developed in Nelms et al (2019) and Patlewicz et al (2018). For the substances assigned into the 3 Cramer classes, the 5th percentiles were calculated from the empirical cumulative distributions of No observed (adverse) effect level (concentration) values. The 5th percentiles were converted to their respective TTC values and compared with published values reported by Escher et al (2010) and Carthew et al (2009). The TTC values derived from ToxValDB were orders of magnitude more conservative, further Cramer classification was not found to be effective at discriminating potencies. Instead, use of aquatic toxicity modes of action such as Verhaar et al (1992) were found to be effective at separating substances in terms of their potencies and new TTC thresholds were derived.